Healthy minds, healthy schools : strategies and activities for happy and successful learners - Montreuil, Tina C., ....- (Toronto : Canadian Scholars, 2017)
Aimed at improving children's social, emotional, behavioural, and academic functioning, Healthy Minds, Healthy Schools provides students at the elementary level with practical, everyday strategies to combat stress, anxiety, and depression. Comprised of 16 sessions, this curriculum-based program demonstrates the universal need for policy-oriented approaches to school-based mental health. A number of components are integrated throughout, including: emotional regulation and expression; mindfulness and metacognition; the link between thoughts, feelings, and bodily sensations; acceptance and self-compassion; goal-directed behaviours; problem solving; and conflict resolution. With guided instruction, sections on personal reflection, and group activity exercises, this essential resource equips children with tools to develop improved attention, inhibition, and cognitive flexibility, strengthen their social skills, and enhance their academic performance.